1999
DOI: 10.1038/990141
|View full text |Cite
|
Sign up to set email alerts
|

A telomerase component is defective in the human disease dyskeratosis congenita

Abstract: The X-linked form of the human disease dyskeratosis congenita (DKC) is caused by mutations in the gene encoding dyskerin. Sufferers have defects in highly regenerative tissues such as skin and bone marrow, chromosome instability and a predisposition to develop certain types of malignancy. Dyskerin is a putative pseudouridine synthase, and it has been suggested that DKC may be caused by a defect in ribosomal RNA processing. Here we show that dyskerin is associated not only with H/ACA small nucleolar RNAs, but a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

35
884
3
11

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,046 publications
(933 citation statements)
references
References 27 publications
35
884
3
11
Order By: Relevance
“…23 A prime candidate gene for this X-linked mechanism is DKC1 encoding dyskerin, which is important for the function of telomerase and has been found to cause congenital dyskeratosis that is characterized by short telomeres. 43 However, if an X-linked mechanism is in effect, a Relationship a n r P -value n r P -value n r P -value n r P -value n r P -value Family effects in telomere length L Broer et al stronger father-daughter correlation would be expected, compared with the father-son correlation, which we did not observe. Other potential explanations for the larger mother-offspring correlation include mitochondrial DNA or other parent-specific 'imprinting' .…”
Section: Discussioncontrasting
confidence: 55%
“…23 A prime candidate gene for this X-linked mechanism is DKC1 encoding dyskerin, which is important for the function of telomerase and has been found to cause congenital dyskeratosis that is characterized by short telomeres. 43 However, if an X-linked mechanism is in effect, a Relationship a n r P -value n r P -value n r P -value n r P -value n r P -value Family effects in telomere length L Broer et al stronger father-daughter correlation would be expected, compared with the father-son correlation, which we did not observe. Other potential explanations for the larger mother-offspring correlation include mitochondrial DNA or other parent-specific 'imprinting' .…”
Section: Discussioncontrasting
confidence: 55%
“…These genes could be categorized into nine groups based on their predicted functions, namely those involved in apoptosis, cell cycle, immune response, telomere maintenance, cell adhesion, transport, metabolism, signal transduction and transcription (Figure 5a). Expression levels of representative genes from various functional categories including dyskeratosis congenital 1 gene (DKC1), 19 target of methylation-induced silencing 1 (TMS1), 20 regulatory factor X-associated protein (RFXAP), 21 NCAM1, 22 and SOCS1 23 were validated by semiquantitative RT-PCR. In general, the RT-PCR data were consistent with the microarray data ( Figure 5b and c and Table 2).…”
Section: Raav-htertc27 Treatment Induces Differential Expression Of Gmentioning
confidence: 99%
“…DKC1 is crucial for telomere maintenance because it is required for the correct intranuclear trafficking of hTERC (or hTR), the RNA component of the hTERT holoenzyme. 19 Mutation of DKC1 leads to a diseased condition known as X-linked dyskeratosis congentita, which is characterized by abnormal pigmentation, bone marrow failure and an increased susceptibility to cancer. 38,39 Recently, Cayuela et al 40 has shown in transgenic TERT/ TERC À/À mice that the increased expression of TERT, in the absence of TERC genetic background, leads to reduced tumorigenesis, indicating that the tumor-promoting effects of TERT overexpression require the formation of TERT-TERC complexes.…”
Section: Raav-htertc27 Treatment Induces Differential Expression Of Gmentioning
confidence: 99%
“…Mutations in dyskerin, which is involved in ribosomal RNA processing 3 and in the telomerase complex 4 , are responsible for the X-linked form of this disease 5 . Families with autosomal dominant inheritance of dyskeratosis congenita (AD-DC) have mutations in the gene encoding the RNA component of telomerase (TERC) 6 .…”
mentioning
confidence: 99%